Synthesis Of Furfural From Xylose Using Carbon Based Bi-Functional Solid Acid Catalyst In Biphasic System - Megersa, Taddesse (ASTU, 2022)
Furfural As Versatile Organic Compounds Is Considered As Xylose Derived Product Via Dehydration Reaction. The Purpose Of This Study Was To Synthesize Furfural From Xylose Using Carbon-Based Bi-Functional Solid Acid Catalyst From Flax Straw And In Biphasic Or A Mixed Solvent Consisting Of Water And 2-Methyl Tetra Hydro Furan. The Carbon Based Bi-Functional Catalyst Was Prepared By Impregnation-Carbonization Followed By Suffocation Methods. The Characterization Of Biochar, Al-Biochar, And Sulfonated Al-Biochar Catalyst Were Carried OutBy Using Brunauer Emmet Teller (Bet), Fourier Transform Infrared Spectroscopy (Ft-Ir), X Ray Diffraction (Xrd), Thermo gravimetric Analysis (Tga), And Sem (Scanning Electron Microscopy). The Surface Area, Total Acid Density And So3h Density Of The Sulfonated Al Biochar Catalyst Were 516.03 M2/G, 4.767 + 0.23 Mmol/G And 1.033 + 0.1 Mmol/G, Respectively. The Result Of Ftir Indicated That The Presence Of The Different Functional Groups Such As Phenolic Group (-Oh), Carboxylic Group (-Cooh), Sulfoxide Group (-So3h) And Al O-Al On The Surface Of Prepared Catalyst. The Effects Of Dehydration Reaction Parameters (Reaction Temperature, Reaction Time, And Catalyst Loading) On The Formation Of Furfural Were Studied. The Maximum Furfural Formation Was Obtained At 180 Oc, 2 Hr And 0.2 Gm Of Catalyst Loading. The Result Of Hplc Revealed That The Furfural Yield And Selectivity Were 64.7%, And 88.0% Respectively. The Ftir Result Also Showed That The Presence Of Conjugated Carbonyl Groups At A Band Intensity Of 1710 Cm-1And Aldehyde Functional Groups At Wavelength Of 2884 Cm-1And 2947 Cm-1That Confirmed The Formation Of Furfural. In General, The Conversion Of Xylose Into Furfural Has Been Successfully Achieved.
Keywords: Bi-Functional Solid Acid Catalyst, Dehydration, Furfural, And Xylose